2021
DOI: 10.1101/2021.10.24.21265453
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of valganciclovir therapy on severe IRIS-Kaposi Sarcoma mortality: an open-label, parallel, randomized controlled-trial

Abstract: High HHV-8 viral load (VL) in Kaposi Sarcoma (KS) has been associated with severe Immune reconstitution inflammatory syndrome (S-IRIS-KS), which can occur after initiating cART, and is linked with high mortality particularly in patients with pulmonary involvement. We investigate if valganciclovir initiated before cART decreases HHV-8 VL and assess if it reduces the incidence of S-IRIS-KS and its attributable mortality. Methods: Open-label parallel-group randomized clinical trial in AIDS cART naive patients wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Volkow et al (9) note the following in their article on the mortality in severe Kaposi's syndrome: In HIV-infected patients who receive ART, the HIV RNA in the blood plasma may not be detectable using the simple laboratory tests, but there is still a reservoir of potentially HIVinfected cells that can reappear after stopping ART. Maintenance of the HIV reservoir may depend on the duration of the existence of the CD4+ T-cell memory that is in the resting phase (G0).…”
Section: Discussionmentioning
confidence: 99%
“…Volkow et al (9) note the following in their article on the mortality in severe Kaposi's syndrome: In HIV-infected patients who receive ART, the HIV RNA in the blood plasma may not be detectable using the simple laboratory tests, but there is still a reservoir of potentially HIVinfected cells that can reappear after stopping ART. Maintenance of the HIV reservoir may depend on the duration of the existence of the CD4+ T-cell memory that is in the resting phase (G0).…”
Section: Discussionmentioning
confidence: 99%
“…The DKS/HIV patients are part of a cohort nested in a clinical trial recruited and followed up at Instituto Nacional de Cancerología, Mexico City (ClinicalTrials.gov, NCT03296553, registered 28 September 2017); patients were enrolled during 2017–19 [ 15 ]. Twenty men > 18 years old with disseminated KS, cART naïve, were randomly assigned to two groups; 10 patients received CT at week 0 (W 0 ), according to current Mexican Guidelines, the cART consists of a triple combination of Efavirenz/emtricitabine/tenofovir.…”
Section: Methodsmentioning
confidence: 99%
“…In this regard, valganciclovir (VGC) has been proposed as an HHV-8 therapy to diminish viral replication in disseminated KS/HIV+ (DKS/HIV) patients and decrease mortality attributable to severe immune reconstitution inflammatory syndrome KS (S-IRIS-KS) episodes [ 13 , 14 ]. A phase II clinical trial conducted by the Instituto Nacional de Cancerología at Mexico City (NCT03296553) established a novel therapy scheme using VGC, delaying 4 weeks of the cART administration, in order to decrease HHV-8 viral load (VL) before initiating cART [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The randomized clinical trial conducted by Volkow et al on 38 ART naïve patients with disseminated KS found a reduction of severe KS-IRIS events and in the number of patients with at least one severe KS-IRIS episode. Valganciclovir treatment was administered at 900 mg BID, initiated four weeks before ART and maintained for 48 weeks [ 106 ]. This result remains to be confirmed in a larger number of patients, and the benefits and risks of such a prophylaxis weighed, particularly due to valganciclovir’s haematological toxicities.…”
Section: Prevention Of Ks-irismentioning
confidence: 99%